Posterior Fossa Intradiploic Epidermoid Cyst: A Case Report - WP, Ng; BS, Liew; TS, Gee; KR, Azmin (IIUM Medical Journal Malaysia, 2015)
Epidermoid cysts are rare, benign congenital tumours of ectodermal origin which typically present between the third to fifth decade. These tumours comprise approximately 0.2-1.8% of all intracranial tumours. Though these pearly tumours are potentially curable, subtotal resection may lead to catastrophic complications such as recurrence, granulomatous meningitis and carcinomatous degeneration of cyst wall. We herein report the case of a 36-year-old man who presented with an unusual mixed density posterior fossa epidermoid cyst on imaging studies. Total removal not only cures both tumour and seizure attack in this case but also preserves patient’s neurological function.